Burrowing behavior of Chironomus yoshimatsui larvae as an indicator of freshwater quality. (February 2018) - Mo, Hyoung-ho; Son, Jino; Ryoo, Keon-Sang; Bae, Yeon Jae; Cho, Kijong
Highlights: The larval burrowing behavior of Chironomus yoshimatsui is ecologically important. The burrowing behavior was affected by cadmium at sub-lethal concentrations. A test method and index were developed to assess freshwater quality using burrowing behavior of C. yoshimatsui larvae. The proposed test indicates the presence of hazardous compounds at sublethal concentrations. Abstract: A new behavioral endpoint in ecotoxicity testing, burrowing behavior of Chironomus yoshimatsui larvae that survived pre-exposure to 0, 1, 5, and 10 mg/L of cadmium for 96 h was evaluated in a system composed of clean reconstituted water and sand for 5 h, at 30 min intervals. The effective time required for 50% of the introduced larvae to burrow (ET50 ), the proportion of the maximum burrowing rate reached during a 5 h period (BR5h ), and the area under the curve at 5 h (AUC5h ) were calculated based on the fitted relationship between burrowing rate and elapsed time. These effect parameters were chosen because they take into account either the burrowing speed of the larvae (ET50 ), or the proportion of the maximum burrowing rate reached during a 5 h period (BR5h ), or both (AUC5h ). We found that higher cadmium concentrations resulted in longer ET50 and lower AUC5h values. Additionally, field water samples were collected from streams near residential, natural, agricultural, and industrial areas in Ansan City, Korea in 2014 and 2015, and were used to validate the proposed burrowing test method. The results of the burrowing tests with field collected water samples also confirmed the sensitivity of burrowing activity as an ecotoxicity endpoint, indicated by the large differences among the ET50, BR5h, and AUC5h across the sampling sites and dates with industrial sites strongly affecting burrowing behavior. This study clearly showed that the proposed burrowing test could provide information that would not be detected with the existing acute toxicity tests, within a relatively short time, and can therefore be used as a complement to existing chemical analyses and acute toxicity tests.